Building Resilience Together: Enhancing Community Preparedness for Flood Disasters in Meteseh Semarang - Lidya Rizki Safitri; Anang Widhi Nirwansyah (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
ABSTRACT This study examines community preparedness for flood disasters in Dinar Indah, Meteseh Subdistrict, Semarang Municipal. Through qualitative analysis of data collected from 14 informants via in-depth interviews and observations, the study identifies various aspects of community preparedness. Additionally, the study highlights the importance of community cooperation and the implementation of emergency response plans, such as disaster management organizations, evacuation plans, simulations, and evacuation reports. The study reveals that the current warning system in Dinar Indah relies on traditional methods, such as kentongan (traditional instrument), electricity poles, and mechanical flood early warning tools. To address the challenges faced in Dinar Indah, the community mobilizes resources through human resources, funding, stakeholder coordination, and technical guidance. In summary, this research investigates community preparedness for floods in Dinar Indah, Semarang, focusing on key factors like knowledge, attitudes, experiences, vulnerabilities, and essential facilities. It emphasizes the significance of community collaboration, emergency response plans, and the need for an improved warning system. Furthermore, it highlights resource mobilization through human resources, funding, coordination, and technical guidance as vital elements for addressing the issues faced in Dinar Indah.Keywords: Â Knowledge, Preparedness, Flood DisasterÂ